Ongoing randomized clinical trials for the treatment of thrombosis in the antiphospholipid syndrome - Finazzi, G. (Hämostaseologie, 2001)
Thrombotic events are a major clinical problem for patients with antiphospholipid antibodies (APA). However, current recommendations for their prevention and treatment are still based on retrospective studies. Data from large scale, prospective clinical trials are required to ultimately identify the optimal management of these patients. To date, at least four randomized studies are underway. The WAPS and PAPRE clinical trials are aimed to establish the correct duration and intensity of oral anticoagulation in APA patients with major arterial or venous thrombosis. The WARSS-APASS is a collaborative study to evaluate the efficacy and safety of aspirin or low-dose oral anticoagulants in preventing the recurrence of ischemic stroke. The recently announced UK Trial compares low-dose aspirin with or without low-intensity anticoagulation for the primary prevention of vascular events in APA-positive patients with SLE or adverse pregnancy history, but still thrombosis-free. It is hoped that the results of these trials will be available soon since clinicians urgently need more powerful data to treat their patients with the APA syndrome.
Keywords: Antiphospholipid antibodies; lupus anticoagulants; randomized clinical trials